Robust CXCL10/IP-10 and CCL5/RANTES Production Induced by Tick-Borne Encephalitis Virus in Human Brain Pericytes Despite Weak Infection - Prančlová, Veronika; Hönig, Václav; Zemanová, Marta; Růžek, Daniel; Palus, Martin (International journal of molecular sciences, 2024)
Tick-borne encephalitis virus (TBEV) targets the central nervous system (CNS), leading to potentially severe neurological complications. The neurovascular unit plays a fundamental role in the CNS and in the neuroinvasion of TBEV. However, the role of human brain pericytes, a key component of the neurovascular unit, during TBEV infection has not yet been elucidated. In this study, TBEV infection of the primary human brain perivascular pericytes was investigated with highly virulent Hypr strain and mildly virulent Neudoerfl strain. We used Luminex assay to measure cytokines/chemokines and growth factors. Both viral strains showed comparable replication kinetics, peaking at 3 days post infection (dpi). Intracellular viral RNA copies peaked at 6 dpi for Hypr and 3 dpi for Neudoerfl cultures. According to immunofluorescence staining, only small proportion of pericytes were infected (3% for Hypr and 2% for Neudoerfl), and no cytopathic effect was observed in the infected cells. In cell culture supernatants, IL-6 production was detected at 3 dpi, together with slight increases in IL-15 and IL-4, but IP-10, RANTES and MCP-1 were the main chemokines released after TBEV infection. These chemokines play key roles in both immune defense and immunopathology during TBE. This study suggests that pericytes are an important source of these signaling molecules during TBEV infection in the brain.
Keywords: viry klíšťové encefalitidy; Chemokine CCL5; kultivované buňky; pericyty; cytokiny; Encephalitis, Tick-Borne; mozek; Cytokines; Encephalitis Viruses, Tick-Borne; replikace viru; klíšťová encefalitida; Cells, Cultured; Brain; Chemokine CXCL10; Humans; chemokin CXCL10; chemokin CCL5; Pericytes; Virus Replication; lidé